An Interacting Negative Feedback Mechanism in a Coupled Extreme Weather–Humans–Infrastructure System: A Case Study of the 2021 Winter Storm in Texas - Wu, Yaqiao; Yang, Saini; Wu, Jingyan; Hu, Fuyu (Frontiers in Physics, 2022)
Extreme weather has long been a threat to human life and critical infrastructures. Previous studies have focused on the reliability and vulnerability of single or interdependent infrastructures under extreme weather threats. However, knowledge of the interactions between coupled real-world complex systems, especially the cascading failure process induced by external shocks, is essential, but receive less attention. Here, we took the historical winter storm of Texas in February 2021 as a case study and collected multisource data to explore the interaction between humans and power system affected by extreme weather. A connectivity-based network was proposed to analyze connectivity robustness and simulate the cascade of overload failures under random and malicious attacks. The results showed that this network presents higher robustness under random attacks in terms of network connectivity. However, a highly heterogeneous distribution of load was shown in this network, making it particularly vulnerable to attacks and easier to trigger cascading failures. An interacting negative feedback mechanism was discovered in this coupled extreme weather-humans-infrastructure system. Extreme weather events directly caused physical failure in infrastructure, while their impact on individuals stimulated the power demand for heat. An increase in demand further intensified the load on the power network, which induced functional failure in infrastructure systems and finally aggravated the adverse impact on people as end-users in return. This feedback loop inspired us to reconsider the relationship among natural disasters, critical infrastructure and humans. Furthermore, even under the background of climate change, the risk of extreme cold weather on electric infrastructure is still worthy of attention since the fluctuation of yearly minimum temperature outstood in the eastern Texas, where the majority of population and electric transmission facilities are located. Thus, it is noteworthy to integrate the interaction between systems in the vulnerability assessment of infrastructure systems or the impact prediction of intense external shocks in future research.